SERUM BILIRUBIN AND GAMMA- GLUTAMYL TRANSFERASE IN WOMEN SUFFERING FROM MIGRAINE. : J Peop Univ Med Health Sci. 2025:15(3), 18-22. http://doi.org/10.46536/jpumhs/2025/15.03.653 - Haji Khan Khoharo1, Muhammad Akbar Memon2, Fatima Qureshi3, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Migraine is a common health issue of predominantly women than men. It affects the lifestyle of person. New biomarkers need to be addressed for an old problem. OBJECTIVE: To study serum bilirubin and liver enzyme in women suffering from migraine at our tertiary care hospital. STUDY DESIGN: A cross- sectional study, STUDY PLACE: Out- patient and Medicine Department, Isra University Hospital from March 2024 to January 2025. METHODS: One hundred migraine cases and controls were selected according criteria. Women of age 20- 40 years were selected. Visual Analogue Scale (VAS) was used for migraine severity. Volunteers were asked for blood samples. Blood samples were collected in Na-F containing tubes for detecting liver function tests analyzed on Cobas Roche Analyzer. Study variables and statistical analysis was performed on SPSS (22.0) using Student t-test and correlations by Spearman`s testing. Correlation scatter plots were developed on Microsoft Excel sheet. Statistical analysis was taken at P ≤ 0.05 as significant. RESULTS: Total (TB), direct (DB) and Indirect bilirubin (IB) among migraine patients and controls were found 1.01±0.32 vs. 1.35±0.07 mg/dl (P=0.0003), 0.61±0.02 vs. 0.77±0.08 mg/dl (P=0.0002) and 0.13±0.02 vs. 0.28±0.05 mg/dl (P=0.003) respectively. GGT in migraine patients was 77.6±9.3 IU compared to 35.3±5.07 IU in controls. TB, DB and IB show negative correlation with VSA migraine severity while GGT exhibited positive correlation. CONCLUSION: The present study shows reveals bilirubin levels and elevated gamma glutamyl transferase (GGT) in women suffering from migraine.